Effect of Financial Inclusion and Financial Literacy on the Financial Performance of Micro, Small, and Medium Enterprises in Ambon City - Restia Christianty; Conchita V. Latupapua; Syarifa Assyatri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is effect of financial inclusion and financial literacy on the financial performance of Micro, Small, and Medium Enterprises in Ambon City. The type of research used is a quantitative research method. The population in this study is the perpetrators of Micro, Small, and Medium Enterprises in Ambon City who are registered with the cooperatives service with a total of 19,783 micro, small, and medium enterprises actors. So the research sample is 100 respondents. The method of analysis in this study uses multiple linear regression analysis. The results of the study show that financial inclusion has a positive and significant effect on financial performance. Financial literacy has a positive and significant effect on financial performance.